The Application of Head-Up Tilt Test to Diagnose Hemodynamic Type of Orthostatic Intolerance in Children Aged Between 3 and 5 Years - Zou, Runmei; Wang, Shuo; Li, Fang; Lin, Ping; Zhang, Juan; Wang, Yuwen; Xu, Yi; Wang, Cheng (Frontiers in Pediatrics, 2021)
Objectives: The head-up tilt test (HUTT) is a useful tool to assess autonomic function and to reproduce neurally mediated reflex. In this study, we evaluated the use of HUTT in pediatric patients aged 3–5 years with orthostatic intolerance. Materials and Methods: The medical history and HUTT records of 345 (180 males, aged from 3 to 5 years) cases of patients who complained of symptoms of orthostatic intolerance and who visited the Syncope Ward, Children's Medical Center, The Second Xiangya Hospital, Central South University from January 2003 to December 2019, were reviewed retrospectively. Results: Seventy-nine (22.9%) cases had positive responses to complete HUTT (basic HUTT and sublingual nitroglycerin HUTT), while 29 (8.4%) cases had positive responses if only basic HUTT was performed. Sublingual nitroglycerin provocation significantly increased the positive rate of the test (x2= 27.565, P < 0.001). The most frequent hemodynamic response to HUTT was vasoinhibitory type vasovagal syncope (12.2%), Syncope (28.7%), and dizziness (22.6%) were the most common symptoms. Eight cases discontinued the test due to intolerable symptoms without severe adverse events occurring. Conclusions: HUTT was safe and well-tolerated and could be used to diagnose the hemodynamic type of orthostatic intolerance in children aged 3–5 years.